'What a Wonderful Change Have I Undergone…So Altered in Stature, Knowledge & Ideas!': Apprenticeship, Adolescence and Growing Up in Eighteenth- and Nineteenth-Century Ulster. (December 2018) - Calvert, Leanne
Until the late nineteenth century, apprenticeship was the main way in which young people were trained in crafts and trades. Given that most apprenticeship terms lasted approximately seven years, young people could expect to spend a large part of their youth in service to another. Apprenticeship therefore coincided with an important phase in the life cycle of many young men (and women) during this period. A study of apprenticeship not only tells us how young people learned the skills with which they made their future living, it also casts light on the process of 'growing up'. However, we still know little about the everyday lives of apprentices, their relationships with their masters, and how young people themselves understood the transition from adolescence to adulthood. Drawing largely on the diary of John Tennent (1772–1813), a grocer's apprentice who kept a record of his time spent in service, this article aims to broaden our understanding of these themes in eighteenth- and nineteenth-century Ireland. It demonstrates that, for young middle-class men like Tennent, apprenticeship played a key role in the transition from boy to manhood.